Reintroducing Heart Sounds for Early Detection of Acute Myocardial Ischemia in a Porcine Model – Correlation of Acoustic Cardiography With Gold Standard of Pressure-Volume Analysis - Luciani, Marco; Saccocci, Matteo; Kuwata, Shingo; Cesarovic, Nikola; Lipiski, Miriam; Arand, Patricia; Bauer, Peter; Guidotti, Andrea; Regar, Evelyn; Erne, Paul; Zuber, Michel; Maisano, Francesco (Frontiers in Physiology, 2019)
Background – Acoustic cardiography is a hybrid technique that couples heart sounds recording with ECG providing insights into electrical-mechanical activity of the heart in an unsupervised, non-invasive and inexpensive manner. During myocardial ischemia hemodynamic abnormalities appear in the first minutes and we hypothesize a putative diagnostic role of acoustic cardiography for prompt detection of cardiac dysfunction for future patient management improvement. Methods and Results – Ten female Swiss large white pigs underwent permanent distal coronary occlusion as a model of acute myocardial ischemia. Acoustic cardiography analyses were performed prior, during and after coronary occlusion. Pressure-volume analysis was conducted in parallel as an invasive method of hemodynamic assessment for comparison. Similar systolic and diastolic intervals obtained with the two techniques were significantly correlated (Q to min dP/dt vs Q to second heart sound (r2=0.9583, p<0.0001), PV diastolic filling time vs AC perfusion time (r2=0.9686, p<0.0001)). Indexes of systolic and diastolic impairment correlated with quantifiable features of heart sounds (Tau vs fourth heart sound Display Value (r2=0.2721, p<0.0001) cardiac output vs third heart sound Display Value (r2=0.0791 p=0.0023)). Additionally, acoustic cardiography diastolic time (AUC 0.675, p=0.008), perfusion time (AUC 0.649, p=0.024) and third heart sound Display Value (AUC 0.654, p=0.019) emerged as possible indicators of coronary occlusion. Finally, these three parameters, when joined with heart rate into a composite joint-index, represent the best model in our experience for ischemia detection (AUC 0.770, p<0.001). Conclusions – In the rapidly evolving setting of acute myocardial ischemia, acoustic cardiography provided meaningful insights of mechanical dysfunction in a prompt and non-invasive manner. These findings should propel interest in resurrecting this technique for future translational studies as well as reconsidering its reintroduction in the clinical setting.